Genesis, paleoenvironmental history and landscape interplays of Holocene buried soils in Minas Gerais, Southeastern Brazil - Vieira, Athos Alves; Siqueira, Rafael Gomes; de Souza, José João Lelis Leal; Isminio, Demetrio Angelo Lama; Francelino, Márcio Rocha; Schaefer, Carlos Ernesto Gonçalves Reynaud; Fernandes-Filho, Elpídio Inácio (Geoderma Regional, 2025)
Buried soils are of great relevance for studies that aim to reconstitute paleoclimates, paleovegetation and paleosurfaces. However, very little is known about the genesis and paleoclimate history of buried soils in the Mantiqueira Range, Southeastern Brazil. Therefore, we investigated a toposequence of buried soils near the Serra do Brigadeiro – Minas Gerais State, aiming to comprehend the environmental conditions under which these soils were formed. To this end, we described, classified and analyzed eight pedocomplexes constituted of buried and overlying soils, focusing on their chemical, physical and mineralogical attributes. We also analyzed the isotopic composition (δ13C and δ15N) of organic matter and dated charcoal fragments using radiocarbon (14C) dating. We also dated the Ab horizons using Optically Stimulated Luminescence, aiming to obtain the timing of soil burial. Soils were, in general, acidic, clayey to very clayey, nutrient-poor, and with mineralogy dominated by kaolinite, gibbsite and goethite, typical of tropical soils. Past soils, found in the lower slopes, were buried by colluvial deposits derived from mass movements, mainly triggered during the Mid-Holocene (7500 to 5000 yr BP), possibly under dry and seasonal climates. The slope colluvium consists of highly pedogenized material with a degree of weathering similar to that of the buried soils, which justifies the absence of lithological discontinuities. The δ13C signal, indicating a mixture of C3 and C4 plants, suggests that the colluvial processes were intensified by the presence of more open vegetation, presumably a wooded savanna. The abundant presence of charcoal suggests the frequent occurrence of paleofires, either climate-induced or anthropogenic.